EFFECT OF RUBBER JUMPING PROGRAM ON SELECTED PHYSICAL FITNESS MEASURES IN CHILDREN AGED 10-12 YEARS OLD - Junma, Montree (Journal of Sports Science and Health, 2020)
Purpose : This research aimed to study the effect of rubber jumping programs on physical fitness in children aged 10-12 years. Methods : A total of 40 children volunteered to participate in this study and were randomly allocated into an experimental group (n=20) and a control group (n=20). The experimental group engaged in a 60-min rubber jumping exercise, 3 days a week for 8 weeks. The control group maintained their regular school activity and received no intervention. Before and after training, the physical fitness battery test was administered. Data were presented as the mean and standard deviation and the differences were compared by using Paired t-test (pretest and posttest) and Independent sample t-test (between groups). Results : 1) For the experimental group, the average body weight, height, sit-ups, push-ups, zig-zag run, standing long jump and distance running (1,200 m) were statistically different between pretest (p<.05) and posttest. On the other hand, there were no significant differences in the average of body mass index (BMI), skinfold thickness and flexibility. 2) For the control group, the average of body weight, height, BMI, sit-ups and push-ups were statistical different (p<.05) between pretest and posttest. In contrast, there were no differences in the average skinfold thickness, flexibility, zig-zag run, standing long jump and distance running. 3) After 8 weeks of training, there was only a significant difference (p<.05) in standing long jump between groups. However, no significant differences were observed in other variables. Conclusion : This research demonstrated the beneficial effect of rubber jumping program on physical fitness components especially a standing long jump in children aged 10-12 years.